Implementation Of Problem Based Learning Models In Learning Systems Of Linear Equations Three Variables - Titania Budiman; Victor R. Sulangi; John R. Wenas (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This study investigates whether the use of the Problem-Based Learning model on the Three Variable Linear Equation System increases student learning outcomes. This investigation is quasi-experimental